Seleksi Galur Lactobacillus plantarum untuk Inokulum pada Pembuatan Silase - Muhammad Nur Cahyanto; Shannora Yuliasari; Budi Prasetyo Widyobroto; Tyas Utami (agriTECH, 2008)
Eleven strains of Lactobacillus plantarum have been evaluated for their growth rate and ability to reduce pH during corn ensiling. Ensiling was carried out in small scale using plastic bag for 14 days. Soluble carbohydrate consumption, organic acids production and pH reduction were measured during fermentation. The growth rate of each strain was also determined in liquid medium. All of the 11 strains of L. plantarum tested were able to improve the ensiling process. However, strains T-16, T-25 and S-98 grew in liquid medium faster than the others, and were able to reduce pH of silage quicker than the other strains. The pH of silage inoculated with strain T-16, T-25 and S-98 decreased from about 5.60 to 4.23, 4.45 and 4.40, respectively,  in two days, and to 3.98, 4.05 and 4.03, respectively, after 14 days fermentation. The acetic acid content of silages inoculated with those strains was low. Strains T-16 and T-25 were suitable as potential silage inoculants and their characteristics were comparable to the one isolated from a commercial silage inoculant.ABSTRAKSebelas galur Lactobacillus plantarum telah dievaluasi laju pertumbuhan dan kemampuannya dalam menurunkan pH selama fermentasi pada pembuatan silase jagung. Fermentasi dilakukan pada skala kecil menggunakan kantong plastik selama 14 hari dan diamati konsumsi karbohidrat terlarut, produksi asam organik, dan penurunan pH-nya selama fer- mentasi. Masing-masing galur juga dilihat laju petumbuhan selnya dalam medium cair. Meskipun kesebelas galur yang diuji mampu memperbaiki proses pembuatan silase, akan tetapi galur T-16, T-25 dan S-98 tumbuh paling cepat dalam medium cair dan mampu menurunkan pH silase paling cepat dibanding galur lain. Setelah difermentasi selama 2 hari pH silase yang diinokulasi dengan galur T-16, T-25 dan S-98 turun dari sekitar 5,60 menjadi berturut-turut 4,23, 4,45 dan 4,40 dan pH silase setelah 14 hari mencapai berturut-turut 3,98, 4,05 dan 4,03. Kadar asam asetat pada silase yang diinokulasi dengan ketiga galur tersebut juga tergolong rendah. Galur T-16 dan T-25 berpotensi sebagai inokulum untuk pembuatan silase dan kemampuannya setara dengan galur yang diisolasi dari inokulum silase komersial.